Implementasi Pembelajaran Discovery Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP Pada Materi Bilangan Bulat: Implementation of Discovery Learning to Improve Critical Thinking Skills of Junior High School Students in the Topic of Integers - Ferdian Wahyu Perdana; Asep Sahrudin; Eka Rosdianwinata (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2024)
This study aims to determine whether the implementation of the Discovery Learning Model on Critical Thinking Skills in Mathematics on Integer Material. Students VII (Seven) of SMPN 1 Malingping. The method in this study using quantitative with the experimental plan used in this study is Pretest-Post-test Control Group Design (Sugiyono, 2011). In this design there are two groups that are randomly selected, then given a pre-test to determine the initial condition is there a difference between the experimental group and the control group. The experimental class chosen by the researcher is students of SMPN Negeri 1 Malingping class VII A with a total of 25 students, and as a control class, namely VII B with a total of 25 students in the mathematics subject of Integer material. Based on the results of the study H0 is rejected and Ha is accepted, namely the average learning outcomes of students about the critical thinking skills of students in the experimental class, namely Class VII-A with the Discovery Learning treatment is better than the control class, namely Class VII-B which is given treatment with the Conventional Learning method. So the author concludes "There is a positive influence on students' critical thinking skills by using Discovery Learning media on class VII-A students of SMP Negeri 1 Malingping in the 2023/2023 Academic Year.